Digital Rights Management and Cultural Institutions Case Study: Maine Music Box - Eschenfelder, Kristin R. (My University, 2010)
The Digital Rights Management and Cultural Institutions Project was funded by an Institute of Museum and Library Services (IMLS) grant 04-06-0029-06 to investigate the impact of digital rights management technologies on the development of digital collections in U.S. archives, libraries and museums. The case studies portion of the project identified six exemplary projects that employed a variety of rights management technologies and policies to serve as examples from which other institutions might learn. This case study focuses on the Maine Music Box, The Maine Music Box (MMB) is a digital music library and tool set that provides computer generated musical rendi-tions, images of sheet music, scores, and Scorch software tools for user in-teraction with audio files such as the ability to control playback, tempo, in-strumentation, and key.
Keywords: copyright; technological protection measure; digital rights management; music collection; digital library